PERMASALAHAN SOSIAL BUDAYA DAN ASPIRASI PEKERJA ANAK PADA RUMAHTANGGA PETANI - Bambang Nugroho; Dumasari Dumasari (Universitas Muhammadiyah Purwokerto, 2007)
In doing/conducting productive work to help to to fulfill addition earnings of impecunious farmer household in rural in the reality natural child worker of manner problems of cultural social. Various problems coverage which is gristle to child worker of important paid attention caused by negative impact and positive impact which is directly accepted by child worker in experiencing x'self aktualisasi. Besides problems of cultural social hence majority child worker of circle of rumahtangga farmer also have aspiration manner, related to repair of its life as individual which is ever claimed to can work productively utilize to yield valuable something that of economics.